Characteristics of crush syndrome caused by prolonged limb compression longer than 24 h in the Sichuan earthquake. Issue 8 (17th June 2010) - Chunguang, Zhou; Rigao, Chen; Fuguo, Huang; Chongqi, Tu; Yueming, Song; Guanglin, Wang; Hui, Zhang; Fuxing, Pei; Yan, Kang; Peng, Liang; Ping, Fu; Ye, Tao
Abstract : Background: To assess the characteristics, treatment and outcome of patients with crush syndrome caused by prolonged limb compression longer than 24 h in the Sichuan earthquake. Methods: Following the Sichuan earthquake, 2728 patients were transferred to the West China Hospital of Sichuan University and 157 of those were admitted to the intensive care unit. The medical records of nine severe crush syndrome patients were retrospectively reviewed. Results: The major associated injuries were in the lower extremities. Renal failure and oliguria developed in all patients. Creatine kinase peaked in all patients. Hyperkalaemia was seen in five patients, and six patients developed acidosis. All patients had amputations; five had two limbs amputated. One patient underwent fasciotomy. Adult respiratory distress syndrome developed in four patients and required mechanical ventilation. All patients underwent haemodialysis. Multiple organ failure and sepsis developed in eight patients, but no patients died. Conclusions: Crush syndrome caused by extremely long compression has high rates of renal failure, multiple organ failure, sepsis and amputation. Early transportation and immediate intensive care therapy would have improved the outcome and survival rate.